American Society of Civil Engineers (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1916)
The American Society of Civil Engineers, by a vote of its membership of six to one, has favored the acceptance of the invitation of the three present Founder Societies, namely, the American Society of Mechanical Engineers, American Institute of Electrical Engineers and American Institute of Mining Engineers, to become a, fourth Founder Society and share with the rest the occupancy of the Engineering Societies' Building. Fortified by this vote, the Board of Direction of the American Society of Civil Engineers has caused a contract to be entered into between, that Society and the present Founder Societies and the United Engineering Society. Work has already begun on adding three stories to the Engineering Societies' Building at a cost not to exceed 1250,000. This cost will be borne by the American Society of Civil Engineers, thereby making its contribution approximately equal to that of the other Founder Societies.